Development of teaching materials for writing short stories based on multi-modal through the Glide Apps platform - Hidayat, Arip; Andriyana, Andriyana; Kautsar, Tifani (Universitas Dian Nuswantoro, 2024)
Developing a multimodal short story writing application is an innovative step in improving students' understanding and ability to write short stories. This study aims to develop and test the effectiveness of an application for learning to write short stories through the Glide Apps platform. This study adopts a research and development (R&D) method to develop multimodal short story writing teaching materials through the Glide Apps platform by integrating qualitative and quantitative approaches. The effectiveness test was conducted using a pseudo-experimental method for students of Kuningan University taking the anatomy of fictional prose course through a one-group pretest-posttest design to evaluate the impact of the application. The results of the effectiveness test provide a positive picture of the potential of this application as an effective tool in improving short story writing skills as a whole. This application presents various learning methods, theories, and exercises that gadgets can access flexibly. This application also provides short story writing assignment facilities via email. The results of this study have positive implications, especially in developing innovative learning methods that can improve students' literacy and creativity in writing short stories.